A classification system of intraocular lens dislocation sites under operating microscopy, and the surgical techniques and outcomes of exchange surgery - Hayashi, Ken (Graefes Arch Clin Exp Ophthalmol, 2016)
PURPOSE: The aim of this study was to examine the recent status of intraocular lens (IOL) dislocation according to a classification system based on vertical dislocation position, as well as the surgical techniques and outcomes of IOL exchange surgery. METHODS: The medical records of 230 eyes from 214 consecutive patients who experienced IOL dislocation and underwent exchange surgery between 2006 and 2014 were reviewed. Vertical dislocation sites observed preoperatively under operating microscopy were examined, along with the surgical techniques and outcomes of IOL exchange. RESULTS: Dislocation sites included (1) the anterior chamber (12.2 %), (2) pseudophakodonesis (19.1 %), (3) the anterior vitreous cavity (47.4 %), (4) trap door-like dislocation (dangling in the peripheral vitreous cavity; 16.1 %), and (5) the retinal surface (5.2 %). The IOL retained in the anterior segment was moved onto the iris by pulling it up through the limbal side ports with an anterior vitrectomy (67.8 %), or by pushing it up from the pars plana with an anterior vitrectomy (26.5 %), while the IOL dropped on the retina was lifting it up from the retina after pars plana vitrectomy (5.7 %). Mean uncorrected and distance-corrected visual acuity significantly improved postoperatively (p < 0.0001). Major complications included a marked elevation in intraocular pressure (7.8 %), pupillary capture (6.5 %), and vitreous hemorrhage (2.6 %). CONCLUSIONS: Based on the classification system, approximately 95 % of dislocated IOLs were retained in the anterior segment, and these IOLs were exchanged using an anterior approach through limbal incisions with an anterior vitrectomy. Visual acuity improved significantly, and serious complications were uncommon, probably because the IOL exchange techniques were standardized and simplified without pars plana vitrectomy.